ANTIMICROBIAL EFFECT OF ORGANOTIN COMPOUNDS DERIVED FROM PHENOLIC SCHIFF BASES - Ane Francielly da Silva Santos; José Roberto da Silveira Maia (The Journal of Engineering and Exact Sciences)
Several organotin(IV) derivatives of phenolic Schiff bases were prepared and investigated by spectroscopic methods. These compounds were bioassayed to evaluate their bacterial effect against Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Salmonella typhimurium) microorganisms. Dimeric and monomeric compounds were characterized by infrared in solid state. Metallic centers having penta-, hexa-, and heptacoordination were identified by multinuclear NMR (1H, 13C and 119Sn) in solution. The di- and triorganotin(IV) derivatives were also investigated by conductimetric measurements in methanol, elemental analysis and melting point. The bioassay of these tin(IV) compounds showed that the best resulting activity was against S. aureus for the triphenyltin(IV) phenolic Schiff base derivatives, presenting MICs of 1.1 µM (0.6 mg mL-1) and 2.2 µM (1.3 mg mL-1).